PENGARUH BRAIN GYM (SENAM OTAK) TERHADAP DAYA INGAT DAN KONSENTRASI BELAJAR SISWA MI TARBIYATUS SIBYAN KLITIKAN - Sutanta; Ulfia Rizka Nur Amalia (Jurnal Kebidanan, 2024)
Background: Children's memory and concentration in learning play a very important role in realm of education world. Effective memory and concentration in learning can influence the level of children's achievement. However, it is not uncommon for children to easily experience a decline in memory and concentration in learning due to amount of material that children have to master, which makes the brain get tired quickly and work less than optimally, so that activities are needed that can stimulate brain work and improve children's memory and concentration in learning. One activity that can improve children's memory and concentration in learning is brain exercise. Objective: The objective of this research is to determine the effect of brain gym on memory and learning concentration of MI Tarbiyatus Sibyan Klitikan students. Method: In this research, the method used is quantitative research with a cross sectional approach with a one group pre-test posttest design. The samples taken were 42 using the purposive sampling method. The instruments in this research were the digit span test back and forth and a concentration observation sheet questionnaire. Data processing was carried out using SPSS to obtain the Wilcoxon Signed Rank Test results. Results: The results of the bivariate analysis show that there is a significant influence between brain exercise on memory and learning concentration with a value of p <0.001 (p<0.05), which means that Ho is rejected and Ha is accepted, so there is an influence of brain exercise (brain gym) on strength. remember and concentrate on children's learning. Conclusion: There is an effect of providing brain gymnastics on the level of memory and learning concentration of MI Tarbiyatus Sibyan Klitikan students. Keywords: Brain gym, Memory, Learning concentration